Violence against children and adolescents: profile and tendencies resulting from Law 13.010 - Daniella Fagundes Souto; Luciane Zanin; Glaucia Maria Bovi Ambrosano; Flávia Martão Flório
ABSTRACT Objective: Describing the profile of reported violence against children and adolescents and draw an essay on the initial effects of Law 13.010 on report patterns. Method: Analytic study of reported cases on SINAN - Information System on Reportable Harms (from 2013 to 2015) of violence to individuals under 19, in 53 cities of Minas Gerais. Results: 1,481 cases were reported, 49.2% before and 50.8% after Law 13.010 came to force (p = 0.5501). There was a 7% decrease on female reports and a 27.2% in male reports (p = 0.0055). It was noticed a change in report patterns (p = 0.0023), with a 130.7% increase to neglect/abandonment reports and a 33% decrease to sexual abuse report. Higher rates of violence from the parents happens at the 1 to 9-year-old age group (p < 0.0001). Conclusion: Main victims were women, individuals from 15 to 19 years, with aggression happening within the household; after Law 13.010, changes to patterns of victim and offender profiles and of kind of violence were noticed.